2015
DOI: 10.1111/ppa.12369
|View full text |Cite
|
Sign up to set email alerts
|

Biological control of sclerotinia stem rot of canola using antagonistic bacteria

Abstract: Stem rot caused by Sclerotinia sclerotiorum is a major fungal disease of canola worldwide. In Australia the management of stem rot relies primarily on strategic application of synthetic fungicides. In an attempt to find alternative strategies for the management of the disease, 514 naturally occurring bacterial isolates were screened for antagonism to S. sclerotiorum. Antifungal activity against mycelial growth of the fungus was exhibited by three isolates of bacteria. The bacteria were identified as Bacillus c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…Over last few decades interest in biocontrol against SSR increased, because downfall of chemical pesticides controls the pathogen as well as their impact on environment (Saharan and Mehta 2008). Although several biocontrol agents have been reported to control SSR in different crops (Awais et al 2008;Hu et al 2013;Kamal et al 2015), least information is available on biocontrol of SSR in cauliflower. In an earlier study, B. pumilus SQR-N43 exhibited 68% control efficacy against R. solani in cucumber (Huang et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Over last few decades interest in biocontrol against SSR increased, because downfall of chemical pesticides controls the pathogen as well as their impact on environment (Saharan and Mehta 2008). Although several biocontrol agents have been reported to control SSR in different crops (Awais et al 2008;Hu et al 2013;Kamal et al 2015), least information is available on biocontrol of SSR in cauliflower. In an earlier study, B. pumilus SQR-N43 exhibited 68% control efficacy against R. solani in cucumber (Huang et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The mean disease incidence in the treatment with B. subtilis BY-2 was 8.9-11.8%, while it was 18.1-22.9% in the control. Kamal et al (2015) showed that two applications of B. cereus SC-1 at 7-day intervals significantly reduced the incidence of sclerotinia stem rot of canola (6.5-9.3%), compared with the control (20.0-29.8%).…”
Section: Mcloughlin Et Al 1992mentioning
confidence: 99%
“…In most cases Pseudomonas showed multiple mechanisms in the biocontrol of diseases caused by S. sclerotiorum. Zazzerini 1987;Zhang and Fernando 2004a;Chitrampalam et al 2008;Hu et al 2011;Zeng et al 2012a, b;Monteiro et al 2013;Hu et al 2014;Kamal et al 2015 Bacillus megaterium Hu et al 2013;Hu et al 2014 Bacillus amyloliquefaciens Fernando et al 2007 Bacillus cereus Zazzerini 1987;Kamal et al 2015 Erwinia herbicola (Pantoea agglomerans) Godoy et al 1990b;Yuen et al 1994 Pseudomonas chlororaphis Zhang and Fernando 2004b;Savchuk and Fernando 2004;Fernando et al 2007;Selin et al 2010 Pseudomonas fluorescens Bin et al 1991;Expert and Digat 1995 Pseudomonas putida Expert and Digat 1995…”
Section: Antagonistic Microorganismsmentioning
confidence: 99%
“…Various microbial species are present in the soil, but only few of them have certain advantages and significantly impact on plant growth (Kamal et al, 2015). Studies on the biological control of deleterious rhizosphere microorganisms, identification of plant growthpromoting rhizobacteria (PGPR) and beneficial and harmful effects of microorganisms on plants have received considerable attention in recent years (Dutta et al, 2008;Zhou et al, 2015).…”
Section: Isolation Of Rhizospheric Bacteria and Seed Germination Expementioning
confidence: 99%
“…The bacteria significantly affect the plants when they are sufficient in number. Similarly to biological agents, bacterial inoculations need to reach an optimal amount to show an obvious effect (Yu et al, 2012;Qin et al, 2014;Kamal et al, regulate the EMP pathway. The key enzymatic activities in EMP were unchanged by the growth-promoting Str.…”
Section: Effects Of Inoculation With Rhizobacteria On Soil Environmentmentioning
confidence: 99%